In search of research excellence : exemplars in entrepreneurship - Mitchell, Ronald K.; Dino, Richard N. (Cheltenham, Glos ; Northampton, MA : Edward Elgar Pub., 2011)
This path-breaking book gathers 'best practices' advice from the masters about how to achieve excellence in entrepreneurship research, how to create an outstanding research career and how to avoid the pitfalls that can sidetrack emerging scholars. Combining narratives from the 2009 and 2010 Entrepreneurship Exemplars Conferences, the authors frame the dialogue using person - environment fit theory and present keynote addresses and dialogue sessions that bring together editors and authors to reach into the unexplored corners of the top-tier research craft.
Preface Introduction 1. In Search of Entrepreneurship Research Excellence: A Person - environment Fit Approach Ronald K. Mitchell, Keith H. Brigham, H. Jackson Walker and Richard N. Dino Keynote Contributors 2. Mindful Scholarship Howard E. Aldrich 3. The Missing Conversation Jay B. Barney 4. Entrepreneurship Research and the Maturation of the Field Michael A. Hitt 5. Challenges we Face as Entrepreneurship Scholars Publishing in Top Journals R. Duane Ireland 6. Entrepreneurship Research: Past, Present and Future Patricia P. McDougall 7. Entrepreneurship and Entrepreneurial Opportunity: Made as Well as Found Sankaran Venkataraman 8. Emerging Themes in Entrepreneurship Research: Editors' Keynote 2010 Keynote Editors: Candida Brush (ET&P) Michael A. Hitt (SEJ) R. Duane Ireland (AMJ) Dean A. Shepherd (JBV) Mike Wright (JMS) Moderator: Ronald K. Mitchell Comments editor: G. Thomas Lumpkin Editor/Author Session Contributors 9. Academy of Management Journal Editor: R. Duane Ireland Authors: Tom Elfring and Keith M. Hmieleski Moderators: Ronald K. Mitchell and Michael H. Lubatkin Comments Editor: G. Thomas Lumpkin 10. Academy of Management Review Associate Editor: Mason A. Carpenter Authors: Melissa S. Cardon, Jeffery S. McMullen and Dean A. Shepherd Moderators: Ronald K. Mitchell and John F. (Jack) Veiga Comments Editor: G. Thomas Lumpkin 11. Entrepreneurship Theory & Practice Editor: Candida Brush Author: Jon C. Carr Moderators: Ronald K. Mitchell and John F. (Jack) Veiga Comments Editor: G. Thomas Lumpkin 12. Journal of Applied Psychology Associate Editor: Jing Zhou Author: Maw-Der Foo Moderators: Ronald K. Mitchell and John E. Mathieu Comments Editor: G. Thomas Lumpkin 13. Journal of Business Venturing Associate Editor: Phillip Phan Authors: Dimo Dimov and William Forster Moderators: Ronald K. Mitchell and John E. Mathieu Comments Editor: G. Thomas Lumpkin 14. Journal of Management Editor: Talya N. Bauer Authors: Hao Zhao, Scott E. Seibert and G. Thomas Lumpkin Moderators: Ronald K. Mitchell and Lucy Gilson Comments Editor: Richard N. Dino 15. Journal of Management Studies Associate Editor: Andrew C. Corbett Authors: J. Michael Haynie, Dean A. Shepherd, Jeffery S. McMullen and James O. Fiet Moderators: Ronald K. Mitchell and Michael Lubatkin Comments Editor: G. Thomas Lumpkin 16. Organization Science Editor: Pamela S. Tolbert Author: Wesley D. Sine Moderators: Ronald K. Mitchell and Lucy Gilson Comments Editor: G. Thomas Lumpkin 17. Strategic Entrepreneurship Journal Editor: Michael A. Hitt Authors: Yasemin Y. Kor and Jeffrey J. Reuer Moderators: Ronald K. Mitchell and Elaine Mosakowski Comments Editor: G. Thomas Lumpkin 18. Strategic Management Journal Associate Editor: Joseph T. Mahoney Authors: Elaine Mosakowski and Anne Parmigiani Moderators: Ronald K. Mitchell and Dimo Dimov Comments Editor: G. Thomas Lumpkin Appendices: Conference Context A. Setting the Stage Richard N. Dino, P. Christopher Earley and Ronald K. Mitchell B. Building Your Publishing Career Ronald K. Mitchell C. Worldwide Reach Richard N. Dino D. Where to from Here? Richard N. Dino Exhibits: Background Information Exhibit I. Journal Mission Excerpts Exhibit II. 2009 Conference Schedule in Order of Occurrence References Contributor and Reference Index Subject Index
.
Includes bibliographical references and indexes.
oif 13/06/13
Loan
Keywords: Entrepreneurship -- Research; Entrepreneurship